2006
DOI: 10.1111/j.1365-2362.2006.01736.x
|View full text |Cite
|
Sign up to set email alerts
|

AMP challenge induces a decrease in FENO in asthmatic subjects modulated by nedocromil

Abstract: The AMP challenge caused a reduction in FE(NO) as a result of prior treatment with nedocromil. Aminoguanidine abolished the nedocromil-induced protection on the late reduction in FE(NO), but not on AMP PC(20). Inducible NOS was implicated in the late FE(NO) decrease after the AMP challenge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Earlier studies have found that bronchoconstriction with histamine, hypertonic saline, exercise, or adenosine 5Ј-monophosphate can cause a decrease in FE NO by 20 -40%; that the fall in FE NO is correlated with a fall in FEV 1 ; and that the FE NO will subsequently increase after treatment with albuterol. [23][24][25][26][27] The effect of airway caliber might partially explain the large variability in FE NO measurements at various time points. The relationship between FEV 1 and FE NO must be considered in future investigations of NO in the patient with acute asthma.…”
Section: Discussionmentioning
confidence: 98%
“…Earlier studies have found that bronchoconstriction with histamine, hypertonic saline, exercise, or adenosine 5Ј-monophosphate can cause a decrease in FE NO by 20 -40%; that the fall in FE NO is correlated with a fall in FEV 1 ; and that the FE NO will subsequently increase after treatment with albuterol. [23][24][25][26][27] The effect of airway caliber might partially explain the large variability in FE NO measurements at various time points. The relationship between FEV 1 and FE NO must be considered in future investigations of NO in the patient with acute asthma.…”
Section: Discussionmentioning
confidence: 98%
“…Changes correlate significantly with the percentage fall in FEV 1, suggesting that the decrease in F e NO may be a function of change in airway calibre 89 . However, one study has shown that the NOS2 inhibitor aminoguanidine inhibited the reduction of F e NO with AMP challenge, suggesting a possible role of NOS2 in the AMP‐induced decrease of F e NO 90 . Allergen challenge in atopic asthmatic subjects results in an increase in F e NO in asthma 91,92 associated with an increase in inflammatory cytokines 92 .…”
Section: Fraction Of No In the Exhaled Breath (Feno)mentioning
confidence: 99%
“…89 However, one study has shown that the NOS2 inhibitor aminoguanidine inhibited the reduction of FeNO with AMP challenge, suggesting a possible role of NOS2 in the AMP-induced decrease of FeNO. 90 Allergen challenge in atopic asthmatic subjects results in an increase in FeNO in asthma 91,92 associated with an increase in inflammatory cytokines. 92 The pre-allergen challenge levels of FeNO correlated significantly with the magnitude of the late fall in FEV1.…”
Section: Factors Affecting Feno Measurementsmentioning
confidence: 99%